The National Public Radio station (NPR) Coverage of U.S. Presidential Election Campaigns 2020 (Research drawn from a Ph.D. thesis) - Al Ameri, Ahmed Salah Taher; Al Sammer, Abdul Salam Ahmed (ALBAHITH ALALAMI, 2022)
This study aimed at examining the role played by the media outlets during the coverage of the presidential election campaigns 2020 of the United States of America. The analytical study used through a partial inventory of the research community for almost three months from the announcement of the candidates’ names by the major parties on August 13 to November 6، which is the official election day in the U.S. National Public Radio Station (NPR) to achieve the objectives of the study. The study reached a number of conclusions related to the contents، methods and sources of media coverage of the election campaigns of the 2020 U.S. at the mentioned station، where the researcher proposed a number of recommendations related to the need for Iraqi academic institutions and their researchers to move towardsthe study of media phenomena in non-Arab societies by their original . languages and foreign sources، as well as the need to implement a field studies to find out the dependence of the American audiences on the media in their coverage of the elections campaigns for the presidency of the United States. The researcher proposed several recommendations related to the Iraqi media Outlets and their role in the internal electoral affairs to benefit from the experience of the American media outlets in this field.